(untitled) (Jurnal Bahasa, 2017)
Being a border state, a great variety of dialects and subdialects exist in Perak. However, dialectal influence is not due to location alone. The migration of non-local communities from other areas of the Malay Peninsula has increased the number of Malay dialects in the northern and southern parts of this state. This study was carried out completely through field work involving 58 villages in five districts, and seeks to enumerate the linguistic and non-linguistic factors-in brief, the geolinguistic factors-in dialect variation in Perak. This research was also carried out using GIS technology. GIS is able to further explain the spatial factor in the migration of non-local communities to Perak based on the evidence of lexical data such as air (water), saya (I/me), datuk (grandfather), nenek (grandmother), kamu (you), besar (big), anjing (dog), betis (calf [part of the leg]) and mentah (raw) that clearly show the influences of the Patani Malay, Banjar, Javanese, and Minang dialects. Furthermore, the easily accessible geographical locations of Larut Matang and Selama, Hulu Perak, Kerian, Hilir Perak and Batang Padang, facilitates the settlement of non-local or immigrant communities in these areas. The existence of GIS technology aids in shedding light on dialect dispersal in Perak. Geographical, historical and economical factors, combined with this technology, provide a clearer and more systematic explanation of the spread of dialects. Keywords: migration, lexical, geographical dialect, GIS, spatial